TESTING THE WEBSITE OF SMP NEGERI 2 TULANGAN USING THE BLACKBOX TESTING METHOD - Erlangga Lesmana Putra; Fitri Dwi Fadilah; Megawati Putri Martinez; Kevin Igor Ibnu Listanto; Ahmad Fahriyannur Rosyady (Computer Science Department, Malang National Institute of Technology, 2024)
In today's modern world we cannot undervalue the importance of technology. Likewise with the impact of technology on education in Indonesian society. SMP Negeri 2 Tulangan serves as an example of a school that has utilized information technology by creating a website that has a function to provide information to public. The website is created specifically for SMP Negeri 2 Tulangan of which the function is to provide information and knowledge about SMP Negeri 2 Tulangan. This test will use the blackbox testing method, blackbox testing is a way of testing software by testing the function of an application without testing its internal structure and workings. This test goes through four stages, namely the selection of the system to be tested, determining the expected input and output, testing the system and analyzing the results. In this test, the results obtained were quite satisfying and good, after we tested and we got test results showing that each menu and feature owned by the website could function perfectly and there were no bugs in the system 12. As a result, the website owned by SMP Negeri 2 Tulangan is considered functional and appropriate for its users to use